The meaning-focused coping and patients adaptation to chronic illness — the research report - Załuski, Maciej (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. The Meaning Making Model by Crystal Park and Susan Folkman is supplement of Lazarus’ and Folkman’s the transactional model of stress and coping. The stress after the most disturbing life illness is a cause of the discrepancy between meaning of illness and global meaning. The meaning-focused coping can reduce discrepancies. The growth of human personality can be an effect of coping, it can also reduce stress’s causes. Aim. An attempt to use the meaning making model in study of seriously ill patients. Material and methods. The research covered 52 patients, 16 were treated for oncological illness, and 36 were treated for neurological illness. The research is based on the proprietary Ruminations Scale, Acceptance of Illness Scale, and The Posttraumatic Growth Inventory. Results and conclusions. In the studied group the most of patients were ruminated about meaning-making of illness. Higher rumination was co-morbid with less time between falling ill and a moment of study (less than 10 weeks). The level of acceptance of illness was in accordance with meaning-focused coping, human supports, and personal growth. Nursing Topics 2014; 22 (2): 209–215